Kajian Hermeneutika Kontemporer: Studi Analisis atas Penafsiran Al-Qur’an Nasr Hamid Abu Zayd dan Hassan Hanafi - Muhammad Furqan; Sakdiah Sakdiah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2022)
The term hermeneutics is still very unfamiliar to the majority of Indonesian Muslims, this is considered reasonable because hermeneutics is an imported item that is not known in Islam scientific world. In the Islamic world itself, although there was a lot of resistance to the results of its studies, it did not discourage some contemporary thinkers from adopting it and ignored the various risks it had to bear, such as Nasr Hamid Abu Zayd and Hassan Hanafi. This article aims to reconstruct their thinking on the interpretation of the Qur'an through the study of hermeneutics. This article is literature research using a qualitative approach. Data collection is carried out by studying related textbooks, encyclopedias, journals, and others. The results of the study showed that Nashr Hamid Abu Zaid tried to find a new meaning that was not pronounced in the Qur'an in accordance with the current context by carrying out hermeneutic studies through the theory of text interpretation in two dimensions, namely the theory of meaning (dalâlah) and significance (magzâ). Hassan Hanafi carries out the study of the hermeneutics of freedom with language analysis, historical context analysis and generalizations, that is, raising the meaning of the